Genomic analysis of Colletotrichum camelliae responsible for tea brown blight disease - Linghong Kong; Jiao Chen; Kaili Dong; Karim Shafik; Wenxing Xu (BMC Genomics, 2023)
Abstract Background Colletotrichum camelliae, one of the most important phytopathogenic fungi infecting tea plants (Camellia sinensis), causes brown blight disease resulting in significant economic losses in yield of some sensitive cultivated tea varieties. To better understand its phytopathogenic mechanism, the genetic information is worth being resolved. Results Here, a high-quality genomic sequence of C. camelliae (strain LT-3-1) was sequenced using PacBio RSII sequencing platform, one of the most advanced Three-generation sequencing platforms and assembled. The result showed that the fungal genomic sequence is 67.74 Mb in size (with the N50 contig 5.6 Mb in size) containing 14,849 putative genes, of which about 95.27% were annotated. The data revealed a large class of genomic clusters potentially related to fungal pathogenicity. Based on the Pathogen Host Interactions database, a total of 1698 genes (11.44% of the total ones) were annotated, containing 541 genes related to plant cell wall hydrolases which is remarkably higher than those of most species of Colletotrichum and others considered to be hemibiotrophic and necrotrophic fungi. It’s likely that the increase in cell wall-degrading enzymes reflects a crucial adaptive characteristic for infecting tea plants. Conclusion Considering that C. camelliae has a specific host range and unique morphological and biological traits that distinguish it from other species of the genus Colletotrichum, characterization of the fungal genome will improve our understanding of the fungus and its phytopathogenic mechanism as well.